PENGARUH TRAINING OF TRAINER KESEHATAN GIGI DAN MULUT PADA GURU DAN ORANG TUA TERHADAP PERUBAHAN PERILAKU MENGGOSOK GIGI SISWA SISWI SDIT AL-USWAH - Pargaputri, Agni Febrina; Andriani, Dwi; Parisihni, Kristanti; Priambodo, Nur Tsurayya; Saptaswari, Dianty; Elidasari, Monika; Fauzia, Bunga; Mulawarmanti, Dian; Sari, Rima Parwati; Kusumawardani, Chaterina Diyah Nanik; Setianingtyas, Dwi; Prananingrum, Widyasri; Nafi'ah; Laihad, Fanny M.; Teguh, Paulus Budi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Oral and dental health is an essential aspect of general health that must be maintained from an early age. This study aims to evaluate the impact of the Training of Trainer (ToT) program on dental and oral health for teachers and parents on changing tooth brushing behavior among students at SDIT Al-Uswah Surabaya. The methods used include surveys, training, evaluations, and observations of a tooth-brushing calendar filled out over 21 days. The results showed an increase in knowledge among teachers and parents, as well as positive changes in students' habits of brushing their teeth twice daily. These results highlight the importance of the role of teachers and parents in supporting dental and oral health promotion for children, which is expected to reduce the risk of dental caries in the future.